2018
DOI: 10.1371/journal.pntd.0006331
|View full text |Cite
|
Sign up to set email alerts
|

The non-linear and lagged short-term relationship between rainfall and leptospirosis and the intermediate role of floods in the Philippines

Abstract: BackgroundLeptospirosis is a worldwide bacterial zoonosis. Outbreaks of leptospirosis after heavy rainfall and flooding have been reported. However, few studies have formally quantified the effect of weather factors on leptospirosis incidence. We estimated the association between rainfall and leptospirosis cases in an urban setting in Manila, the Philippines, and examined the potential intermediate role of floods in this association.Methods/Principal findingsRelationships between rainfall and the weekly number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 28 publications
7
40
0
Order By: Relevance
“…This relationship have also been found out from the study conducted by Matsushita et al in Philippines who found out that the risk of post-rainfall, leptospirosis peaked at a lag of 2 weeks (using 0 cm/week rainfall as the reference) with RRs of 1.30, 1.53, 2.45, 4.61, and 13.77 for light, moderate, heavy, intense and torrential rainfall (at 2, 5, 16, 32 and 63 cm/week), respectively. 13 In the study conducted by Pawar et al in Maharashtra rainfall was associated with increasing cases of leptospirosis at a lag of 1-2 months similar to our study. 10 Flooding after rainfall can force humans and rodents into closer contact, which can result in further contamination of surrounding water.…”
Section: Resultssupporting
confidence: 90%
“…This relationship have also been found out from the study conducted by Matsushita et al in Philippines who found out that the risk of post-rainfall, leptospirosis peaked at a lag of 2 weeks (using 0 cm/week rainfall as the reference) with RRs of 1.30, 1.53, 2.45, 4.61, and 13.77 for light, moderate, heavy, intense and torrential rainfall (at 2, 5, 16, 32 and 63 cm/week), respectively. 13 In the study conducted by Pawar et al in Maharashtra rainfall was associated with increasing cases of leptospirosis at a lag of 1-2 months similar to our study. 10 Flooding after rainfall can force humans and rodents into closer contact, which can result in further contamination of surrounding water.…”
Section: Resultssupporting
confidence: 90%
“…Floods can potentially increase the spread of vector-borne diseases, such as leptospirosis, Japanese encephalitis, malaria, dengue, rabies, etc. (Afzal and Sultan, 2013;Ding et al, 2014;Matsushita et al, 2018;Mohd Radi et al, 2018;Saeed and Piracha, 2016;Smith et al, 2013;Zhang et al, 2016). Similar findings have been reported in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Our study identified positive short-term associations of rainfall with leptospirosis at lags of 1 and 2 weeks. Previous work in Manila identified that rainfall was associated with higher number of clinically suspected leptospirosis cases at a lag time of 2 weeks [27]. Reasons for the shorter time lags found in our work may be explained by differences in methodology.…”
Section: Discussionmentioning
confidence: 37%
“…Our study performed active case finding across the study period for ascertainment of clinical leptospirosis, and our findings were confirmed with the gold standard laboratory testing. The study in Manila included only suspected leptospirosis cases [27] with an expected rate of laboratory confirmation of 54% [44]. Correct estimates of this time lag between rainfall and disease incidence are important for accurate prediction of short-term leptospirosis risk and accurately direct public health interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation